Gender, Age, Marital Status, and Education as Predictors to Quality of Life in Elderly: WHOQOL-BREF Indonesian Version - Gondodiputro, Sharon; Hidayati, Aghnia Rizki; Rahmiati, Lina (Faculty of Medicine Universitas Padjadjaran, 2018)
Objective: To analyze the quality of life in elderly with regards to gender, age, marital status, and education.Methods: An analytical study involving 88 (eighty eight) elderly who lived in 6 villages in the suburb area of Jatinangor sub-district, West Java, Indonesiawas performed in June 2017. The inclusion criteria were men and women, ≥60 years old, able to communicate in Indonesian, and a mini mental state examination (MMSE) score of ≥23. The variables in the study were gender, age, marital status, and education. Quality of life (QoL) was measured using translated WHOQOL-BREF. Collected data in the study were analyzed statistically using Chi square, Mann-Whitney, Friedman, Post hoc using Wilcoxon, and Kruskal-Wallis tests.Results: The study discovered that all of the respondents had low QoL score (≤60). The lowest score was the result of physical domain. There was no significant QoL difference between men and women (p>0.05) but a significant QoL difference regarding to age, marital status and education level was found in the study (p˂0.05).Conclusions: Elderly in suburb area has low QoL and there is a difference in Qol based on age, marital status, and educational level.Keywords: Education level, elderly, gender, marital status, quality of life DOI: 10.15850/ijihs.v6n1.1201